2021
DOI: 10.3390/app11178058
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Paper Resistance against Moisture and Oil by Coating with Poly(-3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) and Polycaprolactone (PCL)

Abstract: Surface hydrophobicity and grease resistance of paper may be achieved by the application of coatings usually derived from fossil-oil resources. However, poor recyclability and environmental concerns on generated waste has increased interest in the study of alternative paper coatings. This work focuses on the study of the performances offered by two different biopolymers, poly(3-hydroxybutyrate-co-3hydroxyvalerate) (PHBV) and polycaprolactone (PCL), also assessing the effect of a plasticizer (PEG) when used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…This approach is much more favorable when compared to other strategies that involve chemical modification of the paperboard fibers or blending in of additives and particles. A few cases following the approach of hydrophobic/hydrophilic barrier coatings have been reported, for example, a waterborne coating based on chitosan- graft -castor oil copolymer applied on paper where chitosan improved the oil resistance and the grafted castor oil increased the hydrophobicity resulting in good water resistance . Another example is a waterborne suspension of whey protein concentrate, beeswax, and sucrose applied on paper, which shows a good barrier for both water and oil.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is much more favorable when compared to other strategies that involve chemical modification of the paperboard fibers or blending in of additives and particles. A few cases following the approach of hydrophobic/hydrophilic barrier coatings have been reported, for example, a waterborne coating based on chitosan- graft -castor oil copolymer applied on paper where chitosan improved the oil resistance and the grafted castor oil increased the hydrophobicity resulting in good water resistance . Another example is a waterborne suspension of whey protein concentrate, beeswax, and sucrose applied on paper, which shows a good barrier for both water and oil.…”
Section: Introductionmentioning
confidence: 99%
“…In the coating formulation, PCL and glycerol concentration were kept constant, respectively at 5% w/v and 4% w/w PCL dry weight, whereas the amounts of agar, starch, and PEG were varied among selected ranges from previous preliminary tests [11]. Taking into account 3 variables in the coating formulations, a full factorial design was implemented having a total of 12 different coating formulations, each one repeated at least three times for replication.…”
Section: Coating Preparationsmentioning
confidence: 99%
“…Several studies have demonstrated that different biodegradable polymers, such as polylactic acid (PLA), polycaprolactone (PCL) or poly 3-hydroxybutyrate-co-3-hydroxyvalerate (PHBV), starch, chitosan and polysaccharides, can be used as barrier coatings for food-packaging paper [8][9][10]. Among those, PCL has been deeply studied as it is a linear thermoplastic aliphatic polyester, partially crystalline, hydrophobic and biodegradable with good mechanical properties and high extensibility [11,12]. Sundar et al [13] demonstrated that coatings containing PCL (5-25%) reduce the water vapor transmission rate (WVTR) of coated paper by 25% compared to uncoated ones and increase the oil/grease resistance value, reaching a 12/12 score for the TAPPI test kit.…”
Section: Introductionmentioning
confidence: 99%
“…PCL exhibits poor oxygen permeability (OP) and water vapor permeability (WVP) properties which limit its application as a coating material, although it has excellent flexibility and toughness [ 20 ]. PCL shows WVP and OP values of ~ 120 g·mil/m 2 day kPa and ~ 1600 cc·mil/m 2 day atm, respectively [ 32 ]. In general, PCL blended with the high barrier biopolymers and nanocomposites are used to increase their barrier properties without disturbing their strength properties [ 20 ].…”
Section: Biodegradable Polymers For High Barrier Paper Coatingmentioning
confidence: 99%